2022
DOI: 10.2147/rru.s375582
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay and Preferences Among Patients Undergoing Cystoscopies: Results from a Large Survey-Based Study in Spain

Abstract: Purpose Cystoscopy procedures can cause distress among patients. Patient perspectives on health services are essential inputs in decision-making. This study investigated the patient preferences in Spain regarding single-use cystoscopes (SUC) compared to reusable cystoscopes and their willingness to pay (WTP) for cystoscopy procedures. Patients and Methods Between May and June 2021, an anonymous survey was distributed to Spanish patients who had previously undergone a cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It seems likely that the trends in urology will also be upward. Borja Brugés et al evaluated patient preferences on having SU or RU flexible cystoscope and found 88% of respondents to opt for the former 64 . There are number of modifications and upgrades that are likely to occur over the coming decade and beyond.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems likely that the trends in urology will also be upward. Borja Brugés et al evaluated patient preferences on having SU or RU flexible cystoscope and found 88% of respondents to opt for the former 64 . There are number of modifications and upgrades that are likely to occur over the coming decade and beyond.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Borja Brugés et al evaluated patient preferences on having SU or RU flexible cystoscope and found 88% of respondents to opt for the former. 64 There are number of modifications and upgrades that are likely to occur over the coming decade and beyond. This includes introduction of wireless connection, suction and development of smaller image sensor chips allowing for reduction in tip dimensions.…”
Section: Future Perspectivesmentioning
confidence: 99%